Screening Packaging and Biologically Active Cushioning Materials for Postharvest Storage of Litchi - Alam, Masood; Singh, J P; Yadav, S K; Siddiqui, M W (Journal of Postharvest Technology, 2014)
Keeping litchi fruits in its own leaves during marketing is a  common practice that provides postharvest protection to the fruits  from weight and colorloss. Considering this common practice, the  present experiment was carried out to evaluate different  combinations of cushioning and packaging materials for  enhanced shelf-life and fruit quality of litchi. The results revealed  that the litchi fruits stored without stalks in CFB boxes, cushioned  with green cassia (Cassia alataL.) leaves recorded the best  postharvest quality throughout the storage. The treatment was found the most effective in curtailing physiological loss in  weight, browning, and acidity with higher retention of TSS. The  fruits kept with stalks in CFB boxes, cushioned with green cassia  leaves ranked second in merit, however, it was found effective in  reducing spoilage loss of fruitswith higher values of total sugars  and ascorbic acid. Begusarai, East and West Champaran and  Bhagalpur districts.
Keywords: Litchi chinensis; Cushioning; Packaging; Storage; Pericarp browning